Convergência das taxas de juros no mercado de crédito bancário brasileiro: um estudo nas modalidades cheque especial e crédito pessoal - Ayres, Vladimir de Almeida (2013)
This study aims to verify whether there is convergence in the Brazilian banking credit market between the arrangements for overdraft and personal loans from banks in the public sector and those banks belonging to the private sector. To reach these results interest rates were collected from the Central Bank website on the Internet from February 2009 to December 2010. Statistical and econometric calculations were used through the observation and verification of ADF and KPSS Unit Root Tests for the series formed by the ratio of the interest rates of banks in the public and private sectors. It is hoped to collaborate with a view which does or does not support the thesis that the federal government can use public banks to regulate interest rates in the Brazilian banking credit market. The results indicate a convergence on the part of the private banks and a divergence by the public ones. It was noteworthy that the results were differentiated in the two modalities studied.